2015
DOI: 10.1021/acs.biomac.5b00852
|View full text |Cite
|
Sign up to set email alerts
|

Materials from Mussel-Inspired Chemistry for Cell and Tissue Engineering Applications

Abstract: Current advances in biomaterial fabrication techniques have broadened their application in different realms of biomedical engineering, spanning from drug delivery to tissue engineering. The success of biomaterials depends highly on the ability to modulate cell and tissue responses, including cell adhesion, as well as induction of repair and immune processes. Thus, most recent approaches in the field have concentrated on functionalizing biomaterials with different biomolecules intended to evoke cell- and tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
164
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 264 publications
(167 citation statements)
references
References 163 publications
(360 reference statements)
3
164
0
Order By: Relevance
“…3G); (3) DA is biocompatible and relatively nontoxic to the human body (Fig. 2J); and (4) the assembly process of AgNPs is simple and mild at room temperature 33, 40 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3G); (3) DA is biocompatible and relatively nontoxic to the human body (Fig. 2J); and (4) the assembly process of AgNPs is simple and mild at room temperature 33, 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Inspired by mussel adhesiveness, Messersmith and his colleagues found that dopamine (DA) can undergo oxidative self-polymerization under alkaline conditions to form polydopamine (PD), enabling biomolecular or cellular attachment, and the catechol group in PD has the ability for chemical reduction 33, 34 . The mussel-inspired DA has super adhesive activity and can create a polymerized layer on various surfaces of material 31, 35 .…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] Deposition of PD onto biomaterials (pH = 8.5) is irrespective of their surface chemistry, which accelerated its application onto various substrates from metal to synthetic polymer used in tissue engineering and biochip approaches. [16][17][18] However, majority of these works involved functionalization of rigid and solid materials, and a limited number of studies have been available on soft materials such as hydrogels. [19] In addition, tuning dopamine coating on the hydrogels for modulating attachment and detachment of multiple cell types as a cell sheet has yet to be done.…”
Section: Doi: 101002/adhm201600210mentioning
confidence: 99%
“…Generally, PD coating has been conducted by a single step on solid biomaterials such as TiO 2 and poly(lactic-co-glycolic acid) (PLGA). [17] Prolonged incubation of biomaterials within PD leads to the deposition of greater amounts of PD, and enhanced cell adhesion likely in a PD-concentration-dependent manner. [23,24] However, the harvest and translocation of the cell sheet requires a balance between cell attachment and detachment.…”
Section: Doi: 101002/adhm201600210mentioning
confidence: 99%
“…At the same time, PDA can be used as a platform for grafting various functional molecules to obtain surface‐functionalized materials . It also can be used alone as a matrix material to obtain new materials with special functions . Until now, the applications of PDA have mainly been focused on the preparation of the adhesive, wettability regulation, metallization–inorganic mineralization, bioactivity, and antifouling antibacterial surfaces .…”
Section: Introductionmentioning
confidence: 99%